Towards Education 4.0 And University 4.0 In Algeria - Dou , Abdelbasset (The Journal of Studies in Language, Culture, and Society, 2025)
The rapid advancements of Industry 4.0, driven by artificial intelligence (AI), the Internet of Things (IoT), and automation, have necessitated a transformation in higher education. This shift towards Education 4.0 and University 4.0 aims to align academic institutions with the demands of a technology-driven world, fostering innovation, digitalization, and knowledge-based economies. This paper examines the transformation of Algerian higher education institutions (HEIs) within this context, analyzing the challenges, opportunities, and strategic policies that shape their transition to University 4.0. Algeria has demonstrated commitment to this transformation through increased investments in research, digital infrastructure, and entrepreneurship initiatives. Calling for a national committee to oversee the transition further reflects its strategic approach. However, barriers such as rigid curricula, unequal access to technology, outdated pedagogical models, and limited funding frameworks remain significant obstacles. It is important to assess whether Algerian HEIs will radically transform or incrementally adapt to the University 4.0 model by evaluating higher education policies, funding mechanisms, and governance models. The study concludes that the successful implementation of University 4.0 in Algeria requires structural, pedagogical, and policy reforms that bridge the gap between education, industry, and economic development. Algerian universities can become key drivers of national progress, economic growth, and global competitiveness by embracing global trends while addressing local challenges.